Kebijakan Publik dalam Ekosistem Ekonomi Halal: Penguatan Tata Kelola Fiskal Kebijakan Publik dalam Ekosistem Ekonomi Halal: Penguatan Tata Kelola Fiskal Islam di Era Pascapandemi - Wildana Amin; Moh. Sholehuddin; Sohibul Kirom (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2026)
The COVID-19 pandemic has generated significant economic and social disruptions, exposing the limitations of conventional fiscal policies in addressing inequality and social vulnerability, particularly in Muslim-majority countries. In the post-pandemic era, governments face the dual challenge of economic recovery and the strengthening of sustainable and inclusive fiscal systems. This study aims to analyze the role of public policy in strengthening Islamic fiscal governance as part of the halal economic ecosystem in the post-pandemic context. This research employs a qualitative interpretive approach with a phenomenological paradigm. Data were collected through in-depth interviews, document analysis, and limited observation involving policymakers, Islamic social finance practitioners, and experts in the halal economy. The data were analyzed thematically to capture key patterns and meanings related to policy implementation and governance practices. The findings indicate that Islamic fiscal instruments, particularly zakat and waqf, have contributed to social protection and economic resilience during and after the pandemic. However, their potential has not been fully realized due to weak governance, limited institutional coordination, and the lack of integration between Islamic fiscal instruments and national fiscal policy. Public policy support remains largely normative rather than strategic. The study concludes that strengthening Islamic fiscal governance through integrated public policy is essential for enhancing the effectiveness of the halal economic ecosystem. Integrating Islamic fiscal instruments into national fiscal frameworks can promote equitable, inclusive, and sustainable economic recovery in the post-pandemic era.